(untitled) (Bodhi Path, 2021)
Every philosophical system is goal oriented. Know thy-self is the message of all saints and sages. Life is full of suffering and purpose is enlightenment. There are different names in different schools to that state. Nirvāṇa is in Buddhism and mokṣa in Jainism. Teachings of Buddha and Lord Mahāvīra flourished in India in the 6th -5th Cent. B.C. E. According to them ignorance is the root cause of suffering. Spiritual teacher (guru) plays an important role in the path of liberation in Buddhism, and Jainism and they gave equal importance to theory (pariyatti) and practice (paṭipatti). Apparently, they are pessimistic because the teaching of ‘sarvaṁ dukkhaṁ’ but in substance they are optimistic as there is a path for freedom from suffering. Due to common characteristics between the two religious’ traditions, there is ample scope for comparison. Teaching of Buddha and Mahāvīra are equally useful even today. we find apparent similarities between nirvāṇa and mokṣa there are important differences between the two. So nirvāṇa and mokṣa are not the same but entirely different goals.